Verbal manipulations by means of comparison in commercials - Kondrashova, M.V. (ХНУ ім. В.Н. Каразіна, 2012)
The article focuses on the concept and verbal manipulations by means of comparison methods in commercials. Three main areas of verbal manipulation, kinds of comparisons and purpose of their use in advertising texts are identified. The conclusion is made that comparison methods are widely used as a tool of verbal manipulations in commercials.
В данной статье мы размышляем над понятием и сущностью вербальных манипуляций в рекламе с приемом сравнения. Выделено три основных направления языкового манипулирования, разновидности сравнений и цели их использования в рекламных текстах. Доказано, что вербальные манипуляции с приемом сравнения – широко распространенное явление в сфере рекламы.
Keywords: verbal manipulations; comparison; trope; structure